2017
DOI: 10.19027/jai.16.2.184-192
|View full text |Cite
|
Sign up to set email alerts
|

Potential use of green algae Caulerpa lentillifera as feed ingredient in the diet of Nile tilapia Oreochromis niloticus

Abstract: The high composition of import raw material of fish diet in Indonesia causes feed price expensively and should be replaced using local materials such as green macro algae. It is, therefore, this study aimed to evaluate effect of diet containing the Caulerpa lentillifera, as feed ingredient in the diet of Nile tilapia Oreochromis niloticus. This study consisted of two experiments which were C. lentillifera digestibility test for raw material feed for tilapia and growth performance test of tilapia. C. lentillife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Some studies on edible Caulerpa from the Binuangeun coast have been reported previously, i.e. metabolite (Januar, Wikanta, & Hastarini, 2004;Sihono, Tarman, Madduppa, & Januar, 2018) and nutrition profiles (Putri, Jusadi, Setiawati, & Sunarno, 2017;Suryaningrum & Samsudin, 2019) as well as antioxidant activities (Nursid et al, 2016;Sihono et al, 2018). However, studies on fatty acids, amino acids, heavy metals, and molecular identification of these seaweeds have never been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies on edible Caulerpa from the Binuangeun coast have been reported previously, i.e. metabolite (Januar, Wikanta, & Hastarini, 2004;Sihono, Tarman, Madduppa, & Januar, 2018) and nutrition profiles (Putri, Jusadi, Setiawati, & Sunarno, 2017;Suryaningrum & Samsudin, 2019) as well as antioxidant activities (Nursid et al, 2016;Sihono et al, 2018). However, studies on fatty acids, amino acids, heavy metals, and molecular identification of these seaweeds have never been reported yet.…”
Section: Introductionmentioning
confidence: 99%